ANALISIS PERILAKU AGRESIF SISWA DI SMP LKIA PONTIANAK - Herman, Ria; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractA common problem in this study is "How to illustrate the aggressive behavior of students at SMP LKIA Pontianak". While general purpose of this research is to know "Picture of aggressive behavior of student at SMP LKIA Pontianak".This research method using descriptive method. Form of research used in this research is survey study. The population in this study amounted to 110, with a sample of 30 students who took 25% of the population with random sampling technique. While the technique of data collector used is direct communication technique and indirect communication. Data collection tools used were interviews and questionnaire aggressive behavior.Based on the results of data analysis of aggressive behavior of students in junior high school LKIA Pontianak classified, it can be concluded that, aggressive behavior in junior high school LKIA Pontianak reached 72.46%Keywoard : aggressive behavior, random sampling